The Impact of Study-at-Home During the COVID-19 Pandemic on Myopia Progression in Chinese Children - Ma, Dandan; Wei, Shifei; Li, Shi-Ming; Yang, Xiaohui; Cao, Kai; Hu, Jianping; Peng, Xiaoxia; Yan, Ruohua; Fu, Jing; Grzybowski, Andrzej; Jin, Zi-Bing; Wang, Ningli (Frontiers in Public Health, 2022)
Background: To assess the impact of study-at-home during the COVID-19 pandemic on myopia development in Chinese schoolchildren. Methods: This historical cohort involved two groups with a total of 154 children. The exposed group was formed from 77 children aged 8 to 10 years who studied at home in the 7-month period during the COVID-19 pandemic (follow-up period: January – August 2020) and did not study at home in the 7-month period before the COVID-19 outbreak (baseline period: July 2019 – January 2020). Seventy-seven children who did not undergo study-at-home (baseline period: 7 months in 2015, follow-up period: 7 months in 2016) were included in the control group. Cycloplegic refraction, axial length and uncorrected visual acuity were measured 3 times. The questionnaire mainly focused on collecting visual habits. Results: Myopia progression was similar between the two groups in the baseline period. However, in the follow-up period the exposed group had a greater change in refraction towards myopia (-0.83 ± 0.56 D) than the control group (-0.28 ± 0.54 D; p<0.001). In addition, the exposed group exhibited a significantly greater change in refraction towards myopia in the follow-up period (-0.83± 0.56 D) than in the baseline period (-0.33 ± 0.46 D; p<0.001). Difference-in-difference analysis indicated that study-at-home accelerated the change in refraction towards myopia (t = -0.567; p < 0.001). Conclusions: During the COVID-19 pandemic study-at-home accelerated the change of refraction towards myopia in children.